Effects of Dietary Supplementation of Probiotic and Synbiotic on Broiler Chickens Hematology and Intestinal Integrity - Beski , S.S.M.; Al-Sardary, S.Y.T. (International Journal of Poultry Science, 2014)
A total of 525 d-old male Ross 308 chicks, were obtained from a local hatchery (Jin hatchery, Duhok, Kurdistan region, Iraq) and randomly assigned to five dietary treatments, each with three replicates, 35 chickens per replicate. The birds were reared in floor pens. The five diet treatments were the control (no supplement), diets supplemented with probiotic at 2.5 or 5 g/kg and diets supplemented with synbiotic at 2.5 or 5 g/kg diet. The five treatments were arranged in a completely randomized design. Probiotic and synbiotic were supplemented throughout the 42 d experimental period. Feed and water were provided ad libitum. This study was conducted to investigate the effects of dietary supplementation of probiotic and synbiotic on some haematological and serum biochemical parameters of broiler chicken at 42 d of age. Supplementation the broiler diet with probiotics and synbiotics resulted in a significant (p<0.05) increase in the concentration of Hb. The H/L ratio also reduced due to the addition of supplements to the broiler diets. Supplementation of broiler diet with synbiotic significantly (p<0.05) reduced the concentration of serum cholesterol and LDL of broiler chickens. Histological results showed that broiler chickens that fed on diets supplemented with probiotics and synbiotics have higher villi than control group. Supplementation of probiotic and synbiotics could have positive effects on the productive performance of broiler thereby improving their haematological and intestinal histological aspects.